Stamens and Gibberellic Acid in the Regulation of Flavonoid Gene Expression in the Corolla of Petunia hybrida - Weiss, David (1990)
Stamen removal at an early stage of flower development inhibits anthocyanin synthesis and chalcone flavanon isomerase (CHI) enzyme activity in corollas of Petunia hybrida. The inhibition can be overcome by gibberellic acid (GA(3)) application. Gibberellin also induces anthocyanin synthesis in detached, young green corollas, grown in vitro in a sucrose medium and promotes CHI enzyme activity. Western blot analysis indicates an increase in chalcone synthase (CHS) and CHI protein levels following GA(3) treatment in both the in vivo and the in vitro systems. Northern blot analysis shows a higher level of steady-state mRNAs for CHS and CHI 24 hours after GA(3) application. In corollas from a transgenic plant containing a β-glucuronidase gene driven by a CHI promoter, a sixfold increase of β-glucuronidase activity was measured following GA(3) application. The mode of action of stamens and GA(3) control over flavonoid gene expression is discussed.